Innovation activity of corporations in emerging economies; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Soboleva E. N. Ekaterina Nikolaevna (2016, 2016)
Title screen